2016
DOI: 10.1051/0004-6361/201527704
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the prominence magnetic field and plasma distributions as obtained from 3D whole-prominence fine structure modeling

Abstract: Aims. We analyze distributions of the magnetic field strength and prominence plasma (temperature, pressure, plasma β, and mass) using the 3D whole-prominence fine structure model. Methods. The model combines a 3D magnetic field configuration of an entire prominence, obtained from non-linear force-free field simulations, with a detailed semi-empirically derived description of the prominence plasma. The plasma is located in magnetic dips in hydrostatic equilibrium and is distributed along multiple fine structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Numerical models revealed that filaments are located in magnetic dips within large flux ropes composed of twisted field lines (see e.g. Aulanier & Schmieder 2002;Dudík et al 2008;Gunár & Mackay 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical models revealed that filaments are located in magnetic dips within large flux ropes composed of twisted field lines (see e.g. Aulanier & Schmieder 2002;Dudík et al 2008;Gunár & Mackay 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They have been intensively observed and studied since the 19th century (see e.g., E. Tandberg-Hanssen 1995; Labrosse et al 2010;Mackay et al 2010). It is believed today that the cool dense plasma of prominences is suspended in magnetic flux ropes or sheared arcades due to the upward magnetic tension of the magnetic field (Aulanier et al 1998;Gunar et al 2013;Gunar & Mackay 2016). Observations reveal that even so-called "quiescent" prominences are highly dynamic, consisting of flowing plasma (Zirker et al 1994(Zirker et al , 1998Schmieder et al 2014), plumes, bubbles (Berger et al 2008;Berger et al 2010;Dudík et al 2012;Heinzel et al 2008;Gunar et al 2014) and ubiquitous oscillations and waves (see e.g., Okamoto et al 2007;Schmieder et al 2013;Arregui et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…3.4). This gives us a maximum value for the magnetic field strength of the order of B 2 + B 2 ⊥ ∼260 G, a result still quite high compared to the values found in the literature (Gunár & Mackay 2016).…”
Section: Supporting the Filament Plasmamentioning
confidence: 45%